THERMAL CONDUCTIVITY AND THERMAL DIFFUSITY DETERMINATION OF BEEF WITH TRANSIENT HEAT TRANSFER METHOD - Saputro, Harjono
Beef thermal conductivity value has been determined experimentally by using transient heat transfer method. Transient method is regarded suitable because beef with dimension of 4 x 4 x 4 cm can be classified as semi infinite material. Measurement was conducted on room temperature and the selected beef had thermal equilibrium on that condition, so that the heat transfer was not affected by ambient temperature. Surface temperature that was contacted to beef is chosen between 5 – 10 0C. To achieve contant temperature on the surface, the experimental apparatus was built with cold water circulation which sprayed water jet on the surface contact through nosels. To determine thermal conductivity thermal (k) and thermal diffusity (????), beef specific heat capacity measurement was conducted before with calorimeter. Measurement time was between 0 second to 1000 seconds. For beef with moisture content 73 %, the acquired k value is 0,56 W/m K and ???? is 1,17 x 10-7 m2/s. For beef with moisture content 67.5 %, the acquired k value is 0,21 W/m K and ???? is 4,48 x 10-8 m2/s. The above results are close to the values have been reported in the literatures.